2009
DOI: 10.1007/s00038-009-5410-z
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationships of adolescent physical activity, screen-based sedentary behaviour, and social and psychological health

Abstract: Summary Objectives To examine how adolescent physical activity (PA) and screen-based media sedentary behaviours (SBM) relate to psychological and social health and identify cross-national differences in these relationships. Methods Associations were examined in five regions using two Health Behaviour in School-Aged Children (HBSC) countries from each. Results Self-reported psychological and social health indices such as self-image, perceived health status, and quality of life were positively related to PA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

23
155
2
14

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(194 citation statements)
references
References 37 publications
23
155
2
14
Order By: Relevance
“…However, there are also indications that specific types of screen time can have positive effects on social and mental outcomes 14 . Thus, in addition to understanding the impacts of different types of screen time, other knowledge gaps persist regarding the relationship between these exposures and mental health indicators, such as the gradual relation (dose-response), differences between sexes 15 , and cultural contexts 16 . In this sense, our aim was to analyze the association between screen time (TV, computer, and video-game), mental health, and social relationships in Brazilian adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are also indications that specific types of screen time can have positive effects on social and mental outcomes 14 . Thus, in addition to understanding the impacts of different types of screen time, other knowledge gaps persist regarding the relationship between these exposures and mental health indicators, such as the gradual relation (dose-response), differences between sexes 15 , and cultural contexts 16 . In this sense, our aim was to analyze the association between screen time (TV, computer, and video-game), mental health, and social relationships in Brazilian adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies have long reported negative associations between levels of physical activity and illicit drug use. 4,5 There are also many anecdotal reports suggesting that people in recovery turn to exercise to help maintain abstinence. Exercise has been shown to reduce symptoms of depression and measures of anxiety, and to enhance cognition, 6,7 factors known to contribute to drug relapse.…”
Section: Introductionmentioning
confidence: 99%
“…We also compared the effects of early or late exercise to the effects of access to a locked or unlocked wheel throughout abstinence (days [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. On the basis of the neurobiological data, 29,33,38 we predicted that exercise during early abstinence would cause a greater decrease in cocaine seeking as compared with exercise during late abstinence.…”
Section: Introductionmentioning
confidence: 99%
“…(Iannotti et al, 2009). One of the main reasons for recent scientific interest in SB is the relationship between SB and risk of being overweight or obese.…”
Section: Introductionmentioning
confidence: 99%
“…For example, across countries and age groups, a positive relationship between SB and the number of friends, the time spent with friends, and the quality of peer relationships was found (Iannotti et al, 2009;Kuntsche et al, 2009). …”
Section: Introductionmentioning
confidence: 99%